2015
DOI: 10.1039/c4sc02697g
|View full text |Cite
|
Sign up to set email alerts
|

Annihilation electrogenerated chemiluminescence of mixed metal chelates in solution: modulating emission colour by manipulating the energetics

Abstract: The emissions of the mixed annihilation ECL of metal complexes can be effectively predicted by estimations of reaction exergonicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 56 publications
6
86
1
Order By: Relevance
“…Various ancillary ligands, such as acetylacetonate, avobenzone(avo) [21], 6-methylpicolinate, picolinamide, quinoxalinate [22], 2-(imidazol-2-yl)pyridine [33] and 2-picolinic acid [34] derivatives, have been synthesized and employed to get blue, yellow, green and red Ir(III) complexes. Although the ECL studies of iridium(III) complexes are currently undergoing a great development, the design and synthesis of new luminophores with distinct ECL emission colors and high efficiency are still needed for the application of iridium (III) ECL complexes in multichannel analytical applications [35].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Various ancillary ligands, such as acetylacetonate, avobenzone(avo) [21], 6-methylpicolinate, picolinamide, quinoxalinate [22], 2-(imidazol-2-yl)pyridine [33] and 2-picolinic acid [34] derivatives, have been synthesized and employed to get blue, yellow, green and red Ir(III) complexes. Although the ECL studies of iridium(III) complexes are currently undergoing a great development, the design and synthesis of new luminophores with distinct ECL emission colors and high efficiency are still needed for the application of iridium (III) ECL complexes in multichannel analytical applications [35].…”
Section: +mentioning
confidence: 99%
“…Since the early work of Nishimura [11], Wightman [12], Richter [13], and Kapturkiewicz [14], ECL works on iridium complexes have opened up the possibility in the analytical applications due to their efficient luminescence and tunable emission properties. Many works done by Richter [15,16], Kim [17], Kapturkiewicz [18,19], Ding [20,21], Hogen [22,23], Marcaccio [24] and Zhou [25]et al groups have been made in designing or modifying the ligands of the Ir(III) complexes. It was found that iridium(III) complexes have high efficient PL efficiencies because both singlet and triplet excitations are contributed to PL emission [26,27] and the emission color and emission efficiency can be tuned by changing the ligand identity or composition [28,29].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the efficiency of direct emission from the excited triplet state, T 1 , in a solution phase is believed to be low due to its long radiative lifetime and quenching by radicals or other species (such as molecular oxygen). Therefore, the absence of T-route pathway for metal complexes allows the effective prediction of ECL generation by estimating the exergonicity of the reactions leading to excited states [44].…”
Section: Annihilation Pathwaymentioning
confidence: 99%
“…[12] The emission band in the NIR range (Îœ~600 nm, Figure 2B) may be fine-tuned through modifications of the ligand environment. [13] It results from the relaxation of an excited [Ru(bpy) 3 ] 2+ * triplet state ( τ =650 ns in water), which is accessible through photochemical excitation of [Ru(bpy) 3 ] 2+ or chemical reduction of [Ru(bpy) 3 ] 3+ . In the presence of suitable oxidation and reducing agents, [Ru(bpy) 3 ] 2+ acts as single electron transfer (SET) redox catalyst, which partially emits the reaction energy in the form of photons (Figure 2C).…”
mentioning
confidence: 99%